Bidirectional Puc Converter Based Battery Storage System for Active and Reactive Power Control - Vural, Ahmet Mete (International Journal of Applied Methods in Electronics and Computers, 2025)
Battery storage systems (BSS) play a crucial role in enhancing power quality, reliability, and renewable energy integration. However, multilevel converters used in BSS often face challenges of high component count and capacitor voltage balancing. This study addresses these issues by proposing a single-phase battery storage system based on a seven-level packed U-cell (PUC) converter with two DC-links. Each DC-link is regulated by a bidirectional DC-DC converter, ensuring stable capacitor voltage control and enabling seamless operation in both grid-tied and stand-alone modes under a unified control scheme. Unlike conventional approaches that redesign controllers for different modes, the proposed system only modifies the reference voltage generation for pulse-width modulation. Simulation results confirm effective capacitor voltage balancing, smooth bidirectional active power transfer, and reliable reactive power exchange, allowing the BSS to function as a single-phase STATCOM. Harmonic analysis demonstrates compliance with IEEE 519–2014 standards, ensuring high power quality in grid-tied and stand-alone operation.